Bartter Syndrome Type 4a in an Adolescent With Lower Extremity Pain: A Case Report: Bartter Syndrome and Lower Extremity Pain - Dalirani, Reza; Pourpashang, Paniz; Mirzaee, Mahbubeh; Jamee, Mahnaz (Journal of Pediatric Nephrology, 2023)
Bartter syndrome is a rare genetic disease with 5 subtypes. In Bartter syndrome type 4, patients suffer from deafness and renal dysfunction since infancy. In this report, we introduced a 16-year-old girl with congenital deafness without any previous renal complaints referred to our center due to ankle pain.